2013
DOI: 10.4028/www.scientific.net/amr.671-674.3083
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of the Safety Education for Foreign Laborer in Construction Site

Abstract: In recent years, the number of foreign workers employed on construction sites in Korea has been on the rise, and industrial accidents involving foreign workers have become a social issue. Yet despite this fact, the interest in safety education for foreign workers has still been relatively low. For this reason, the purpose of this study is to analyze the current state of safety education for foreign construction workers. To conduct an analysis of the current status, we surveyed foreign construction workers curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Audiovisual materials were used to facilitate learning in a low-skilled workforce with limited host country language abilities (Evia, 2011; Shin, Nam, Kim, & Kim, 2013; Won, Kwon, Jung, Kim, & Shin, 2013). Harrington et al (2009) reported interactive, practical activities, such as group discussions and tailgate training, were perceived as useful.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Audiovisual materials were used to facilitate learning in a low-skilled workforce with limited host country language abilities (Evia, 2011; Shin, Nam, Kim, & Kim, 2013; Won, Kwon, Jung, Kim, & Shin, 2013). Harrington et al (2009) reported interactive, practical activities, such as group discussions and tailgate training, were perceived as useful.…”
Section: Resultsmentioning
confidence: 99%
“…New challenges appear as digitalization and information and communications technology offer a wider array of options that, when properly designed, may be especially useful for the target population, offering trainees the opportunity to acquire learning at their own pace, potentially with less spoken language. Methods such as e-learning, gamification, behavioral modeling, simulation, practice in “close to real context situations,” social media, experiential learning, and communities of practice may support classroom teaching (Evia, 2011; Forst et al, 2013; Shin et al, 2013; Won et al, 2013).…”
Section: Discussionmentioning
confidence: 99%